Nature, Space and Capitalism in Ngulumapu. The Metabolic Fracture from The Installation of The Malleco Defensive Line, 1867-1878 - Pérez, Víctor Cristóbal (Revista de Historia Social y de las Mentalidades, 2023)
The following essay will examine the restructuring of the geographical space and the transformation of the spatial representations by the State from the installation of the Malleco Defensive Line in the Mapuche territory, during the second half of the 19th century, through the idea of a nature that deserves to be dominated and controlled under the principles of progress and civilization. An attempt will be made to demonstrate how the foregoing produced a functional commodified space for the accumulation of capital, giving shape to a space of catastrophe. From a Marxist perspective, it is argued that the occupation of Mapuche territory marks the metabolic fracture between nature and society, the transition from a pre-capitalist space to a capitalist one, proposing the distinction between the Production of Mapuche Space and the Production of State Space.
Keywords: Nature; Producction of space; Capitalism; Metabolic fracture